Temporal dynamics of pair-rule stripes in living Drosophila embryos. - Lim, B.; Fukaya, T.; Heist, T.; Levine, M. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Traditional studies of gene regulation in the Drosophila embryo centered primarily on the analysis of fixed tissues. These methods provided considerable insight into the spatial control of gene activity, such as the borders of eve stripe 2, but yielded only limited information about temporal dynamics. The advent of quantitative live-imaging and genome-editing methods permits the detailed examination of the temporal control of endogenous gene activity. Here, we present evidence that the pair-rule genes fushi tarazu (ftz) and even-skipped (eve) undergo dynamic shifts in gene expression. We observe sequential anterior shifting of the stripes along the anterior to posterior axis, with stripe 1 exhibiting movement before stripe 2 and the more posterior stripes. Conversely, posterior stripes shift over greater distances (two or three nuclei) than anterior stripes (one or two nuclei). Shifting of the ftz and eve stripes are slightly offset, with ftz moving faster than eve This observation is consistent with previous genetic studies, suggesting that eve is epistatic to ftz The precision of pair-rule temporal dynamics might depend on enhancer-enhancer interactions within the eve locus, since removal of the endogenous eve stripe 1 enhancer via CRISPR/Cas9 genome editing led to precocious and expanded expression of eve stripe 2. These observations raise the possibility of an added layer of complexity in the positional information encoded by the segmentation gene regulatory network.